2007
DOI: 10.1021/jp0674120
|View full text |Cite
|
Sign up to set email alerts
|

Bromine Enrichment in the Near-Surface Region of Br-Doped NaCl Single Crystals Diagnosed by Rutherford Backscattering Spectrometry

Abstract: Bromine released from sea-salt aerosols and seawater ice is known for its high chemical reactivity. Previous studies have suggested that its availability to the gas-phase could be enhanced by segregation processes increasing Br concentration on the aerosol surface as compared to the bulk. However, little is known about the composition within the near-surface region, that is, the outermost approximately 100 monolayers. We used Rutherford backscattering spectrometry (RBS) to measure Br concentration profiles to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 48 publications
1
13
0
Order By: Relevance
“…However, it is now recognized that Br − and I − ions concentrate at the surface of humidified solid salts and deliquesced solutions. This has been shown by ambient pressure electron spectroscopy and Rutherford back scattering studies (Zangmeister et al 2001, Ghosal et al 2005, Hess et al 2007. Molecular dynamics simulations indicate that polarizable species such as Br − and I − associate with the surface more than do less polarizable species such as Cl − and F − (Jungwirth and Tobias 2006).…”
Section: Discussionmentioning
confidence: 79%
“…However, it is now recognized that Br − and I − ions concentrate at the surface of humidified solid salts and deliquesced solutions. This has been shown by ambient pressure electron spectroscopy and Rutherford back scattering studies (Zangmeister et al 2001, Ghosal et al 2005, Hess et al 2007. Molecular dynamics simulations indicate that polarizable species such as Br − and I − associate with the surface more than do less polarizable species such as Cl − and F − (Jungwirth and Tobias 2006).…”
Section: Discussionmentioning
confidence: 79%
“…However, it was also shown that the diffusion constant of Br through the NaCl crystal lattice plays a crucial role in describing the kinetics of the Br surface enrichment. 6 This is basically the motivation for the study presented here.…”
Section: Introductionmentioning
confidence: 87%
“…1 Together with atmospheric radiation, meteorology, and cloud physics, these aerosols strongly affect the chemistry of the atmosphere, e.g., 2-4 the release of chlorides and bromides from sea salt aerosols into gas phase strongly influences the halogen budget and therefore can have a substantial impact on chemistry of hydrocarbons or ozone in the troposphere. 5 In a recent paper, 6 it was shown that partial liquification of the surface of a Br doped NaCl crystal at high relative humidity can lead to an enrichment of Br on the surface compared to bulk. Since chemical reactions between aerosols and the surrounding gas phase occur mainly on the aerosol surface, such discrepancies between the surface and the bulk composition may have significant effect on the chemical composition of the atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…We used Rutherford backscattering spectrometry [5,6] (RBS) to measure the Cl depth profile and the resonant cross section of O at approximately 3.05 MeV [5,6] to measure the O depth profile. A beam of 4 He + ions was used with energies between 3.00 and 3.26 MeV and typical beam currents below 5 nA.…”
Section: Methodsmentioning
confidence: 99%